Analysis of oligomers to assess exposure to microplastics from foods. A perspective - Tsochatzis, Emmanouil D.; Theodoridis, Georgios; Corredig, Milena (Frontiers in Nutrition, 2023)
There is an emerging interest in evaluating the presence of microplastic (MP) and nanoplastic (NP) residues in foodstuff. In spite of their potential threat to human health, there is still a need for harmonized methods to evaluate and quantify their presence. During the manufacture of plastic, incomplete polymerization may occur. Conversely, during chemical, mechanical or enzymatic depolymerization, oligomers form. Oligomers are a few nanometers in size. Recent advances in analytical chemistry have enabled the quantification and identification of these oligomers in various complex biological matrices. We therefore propose that the specific nanosized oligomers may be considered as markers of MPs/NPs presence. This advance can facilitate a broader perspective for assessing MPs/NPs exposure, leading to the evaluation of safety of food and associated risks for humans.